Comparison of simple and rapid extracting methods of free-tags Mycobacterium tuberculosis protein 64 Recombinant Protein from polyacrylamide gel: Electroelution and the optimized passive elution - Sri Agung Fitri Kusuma; Ida Parwati; Toto Subroto; Yaya Rukayadi; Muhammad Fadhlillah; Asep Rizaludin (Wolters Kluwer Medknow Publications, 2021)
In this study, the Mycobacterium tuberculosis protein 64 (MPT64) protein was constructed without any tags to facilitate the purification using column affinity chromatography, but the MPT64 must be obtained as a pure protein. This study was purpose to ensure the efficient extracting method to purify protein MPT64 directly from the polyacrylamide gel. The crude extract of extracellular protein containing MPT64 protein was separated into single protein band and the targeted protein which is located in the size of 24 kDa was excised. Each of the six bands was collected in a sterile microtube to be eluted using electroelution and the optimized of the passive-elution method. Both the elution methods demonstrated the purity level of the MPT64 protein by detecting a solely band on the gel at the 24 kDa. Among the variety of passive-elution time, the highest MPT64 protein concentration was 0.549 mg/ml after elution for 72 h. However, the electroelution result provided higher MPT64 protein concentration, i.e., 0.683 mg/mL. However, based on the recognition of the purified MPT64 protein on commercial detection kit of MPT64 protein, it showed that the positive result was only showed by the passive-elution extracting protein. Therefore, for purifying the protein MPT64 from the sodium dodecyl sulfate-polyacrylamide gel electrophoresis gels, the efficient method was passive elution.